1999
DOI: 10.1063/1.479727
|View full text |Cite
|
Sign up to set email alerts
|

Etching effects during the chemical vapor deposition of (100) diamond

Abstract: Sandia NationalLaboratories Albuquerque+ NM 87185Under botb static and common MAS conditions (< 15 kHz) the question of residual X-Y heteronuclear decoupling can become a complicating factor in the analysis of various Nh4R results. In our -lab the impact of 31P-nNa dipolar coupling on the observed 2%a Mz relaxation for a series of sodium phosphate glasses was recently investigated by employing continuos wave 31Pdecoupling during the entire pulse sequence. Initially these efforts were complicate by the inabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 55 publications
(84 reference statements)
1
46
0
Order By: Relevance
“…The preferentially occurring desorption of CH 3 radicals at flat sites away from step edges as postulated in Ref. [19] may additionally take place. However, surface diffusion of growth species has to be taken into account when trying to explain such extremely flat faces featuring some degree of long distance order of step edges after long growth times at high substrate temperatures.…”
Section: Morphologymentioning
confidence: 84%
“…The preferentially occurring desorption of CH 3 radicals at flat sites away from step edges as postulated in Ref. [19] may additionally take place. However, surface diffusion of growth species has to be taken into account when trying to explain such extremely flat faces featuring some degree of long distance order of step edges after long growth times at high substrate temperatures.…”
Section: Morphologymentioning
confidence: 84%
“…Previous researchers have used quantum chemical methods to model the energy barrier for etching in a variety of microscopic models of the growing diamond surface. 16,29,30 The energy barriers were also used, together with transition-state theory, to obtain microscopic rate constants for etching. The barrier heights are, however, somewhat dependent on the level of quantum-mechanical theory used.…”
Section: Processmentioning
confidence: 99%
“…However, recent theoretical models have shown that the addition of surface diffusion to models would lead to higher growth rates than are experimentally observed [11]. Other mechanisms that have been proposed to explain the growth of smooth diamond (100) films are anisotropic etching [12] and preferential etching of under-coordinated atoms [11]; however, there has not yet been any direct evidence for these processes. In this paper, we report, for the first time, atomic resolution UHV STM studies of the temperature dependence of the etching of epitaxial diamond (100) films by atomic hydrogen, and these results support the anisotropic etching model.…”
mentioning
confidence: 99%
“…Diffusion on the diamond (100) surface during growth has been modeled as occurring along surface sites where hydrogen has been removed by abstraction [10]. However, recent theoretical models have shown that the addition of surface diffusion to models would lead to higher growth rates than are experimentally observed [11]. Other mechanisms that have been proposed to explain the growth of smooth diamond (100) films are anisotropic etching [12] and preferential etching of under-coordinated atoms [11]; however, there has not yet been any direct evidence for these processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation